Penyatuan Penderia Untuk Panduan Robotik - Johar, Haffiz (Universiti Sains Malaysia, 2006)
The purpose sensor fusion in controlling and driving an industrial robot is to enhance robot realiability and efficiencies for automation by using touching sensing element and vision sensing element.The purpose of this project is to built a sensor systems which include touching element and vision element for controlling and driving the movement and coordination of an industrial robot Mitsubishi Movemaster model RV-M1 to pick and placed eggs without breaking them. For this pupose touch sensor and vision is attached to the robot.The coordination and other information for an object can be determined by using a certain software. The touch sensor is used to control the robot gripper without causing any harm to the eggs.The most important thing to running the robot automatically is the communication between robot and computer by using serial communication interface such as RS 232C. This communication device allow to write a command to perform a task to the robot.